Empowering Archaeological Sites In The Mount Watangan Area To Become Special Interest Tourist Destinations - Suwargono, Eko; Hari Murti, Ghanesya; Setiawan, Ikwan; Talapessy, Albert; Subaharianto, Andang (Journal Of Humanities Community Empowerment, 2024)
Mount Watangan in Lojejer Village, Wuluhan District, Jember Regency holds many caves that were once inhabited by humans in the palaeolithic era about 20,000 years ago. There are about 22 caves identified and 8 of them have been studied. The caves are: Sumbersalak Cave, Marjan Cave, Sodong Cave, Macan Cave, Sebanen Cave 1 or Samadi Cave, Lawa Cave 1 and 2, and Maelang Waterfall Cave. With an ecocultural approach, Mount Watangan caves are developed into special interest tourist destinations. This community service activity conducts investigations and exploration of ancient caves to obtain important data related to their existence. The data obtained were discussed in the forum to find important materials as a reference for the implementation of the final activities of service activities. Making creative and strategic event designs for cultural arts as a navigation towards the creation of a tourist destination of special interest to Mount Watangan is the final activity of this service. From the discussion of the results of the investigation and exploration of ancient caves, cultural arts events were formulated that will construct the shape and face of Mount Watangan's special interest tourist destinations. The design of the cultural arts event is: exploring the ancient times; theater performances, / ancient dances; exploration and holding of ancient percussion music; ritual ceremonial activities; collaborative performances of ancient, classical, and modern-contemporary cultural arts; and activities to develop archaeological discourse, culture, and tourism. The implementation of these events is divided into 5 categories in a year, namely: incidental, monthly, quarterly, mid-yearly, and annual events